KEANEKARAGAMAN TUMBUHAN BERBUNGA (ANGIOSPERMAE) DI UNIVERSITAS NEGERI MEDAN - Marpaung, Dwi Ratna Anjaning Kusuma; Puspitasari, Wina Dyah; Handayani, Dina; Simanjuntak, Debora Cantyka Febriani; Pandiangan, Selvi Oktavia; Panggabean, Nurul Huda; Hafzari, Rini; Khairani, Anita (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
A variety of plants are found in the Medan State University (Unimed) campus area which is in the border area of Medan city, precisely in Deli Serdang Regency with an area of Â± 495,000 m2. Flowering plants (Angiosperms) are one of the groups of plants that make up the vegetation on the Unimed campus with various types, characteristics (habitus) and various benefits. These flowering plants not only have aesthetic and ecological value but can also be a learning resources. However, there is no data yet on what types of flowering plants (Angiosperms) are found in the campus area. An inventory carried out in the Unimed campus area obtained 80 species of flowering plants belonging to 71 genera and 33 families. The diversity of flowering plants is dominated by the Arecaceae family with 7 species from the monocot group and 13 species from the Fabaceae family which are included in the Dicot group. The various forms of appearance (habitus) of these flowering plants are herbs, bushes, shrubs and trees and their various uses include ornamental plants, shade plants, fruit-bearing plants and medicinal plants.